Cross-cultural adaptation of the German Pain Solutions Questionnaire: an instrument to measure assimilative and accommodative coping in response to chronic pain - Sielski R; Glombiewski JA; Rief W; Crombez G; Barke A (Journal of Pain Research, 2017)
Robert Sielski,1 Julia Anna Glombiewski,1 Winfried Rief,1 Geert Crombez,2 Antonia Barke1 1Department for Clinical Psychology and Psychotherapy, Philipps-University of Marburg, Marburg, Germany; 2Faculty of Psychology and Educational Sciences, Ghent University, Ghent, Belgium Abstract: According to the dual process model of coping, assimilative or accommodative strategies can be applied to deal with aversive life situations. In people with chronic pain, the tenacious focus on achieving analgesia is often referred to as assimilative coping and associated with more disability and catastrophic thinking. In contrast, accommodative coping (accepting one’s pain and setting new goals) appears to have beneficial effects. To assess how people with chronic pain use these different coping strategies, questionnaires measuring these concepts are needed. Following international guidelines, a German version of the Pain Solutions Questionnaire (PaSol) was prepared. A sample of 165 participants with chronic low back pain (CLBP; 60% women; age 53 ± 8.4 years) filled in the questionnaire and measures for pain-related disability, affective distress, catastrophic thinking, and attention to pain. Item analyses, an exploratory factor analysis, and correlations with pain-related measures were calculated. In addition, data from 98 participants who received psychological treatment were examined to investigate the PaSol’s sensitivity to change. The exploratory factor analysis reproduced the original questionnaire’s four-factor structure. Internal consistencies for the subscales ranged from Cronbach’s α=0.72 to α=0.84. Mean item difficulties for the subscales ranged from pi=0.62 to pi=0.79. The highest correlations were found for Meaningfulness with catastrophic thinking (r=−0.58) and affective distress (r=−0.36). The PaSol subscale Meaningfulness predicted pain-related disability; the subscales Meaningfulness and Solving Pain predicted affective distress. Furthermore, the PaSol was found to be sensitive to detect changes over time. The German version of the PaSol is a reliable and valid instrument in the measurement of assimilative and accommodative coping strategies in people suffering from CLBP. It may provide a useful tool when examining temporal dynamics of the changing coping strategies in the transition from acute to chronic pain as well as during pain treatments. Keywords: acceptance, back pain, coping, problem-solving, German, validation